Diabetes Mellitus Self-Care Education Program Towards Self-Care Patterns And Blood Sugar Control Among Outpatients At Imelda Pekerja Indonesia Hospital - Purba, Lamtiur; Simanjuntak, Samuel M. (Media Karya Kesehatan, 2024)
Globally, Indonesia is ranked seventh with 19.47 million diabetes sufferers and an overall diabetes prevalence rate of 10.6% (IDF, 2021). There are still many diabetes sufferers in the city of Medan and its surroundings who have uncontrolled blood sugar levels. The aim of this research is to provide services to community members suffering from DM through the implementation of the DM Self-Care Education Program and to examine its effect on self-care behavior and blood sugar levels of patients at the Imelda Workers Indonesia RSU Polyclinic in Medan. This research is an experimental study with a sample of 58 patients obtained simply at random. Univariate and bivariate analysis was used with paired sample z-test. The trial results showed that there were significant differences in the self-care patterns of DM patients and the blood sugar levels of DM patients before and after participating in the DM Self-Care Education Program. The research results provide sufficient evidence that the Self-Care Education Program intervention with DSME improves self-care patterns and the blood sugar control   with a p-value of 0.00 < 0.05. The Self-Care Education Program with DSME intervention provides encouragement for self-care awareness and blood sugar treatment for community members with DM. It is recommended that the implementation of self-care be spread to community members via DM in various health service facilities. Keywords: Education, blood sugar self-care, diabetes mellitus.